2017
DOI: 10.1152/ajpendo.00407.2016
|View full text |Cite
|
Sign up to set email alerts
|

Functional high-intensity training improves pancreatic β-cell function in adults with type 2 diabetes

Abstract: Type 2 diabetes (T2D) is characterized by reductions in β-cell function and insulin secretion on the background of elevated insulin resistance. Aerobic exercise has been shown to improve β-cell function, despite a subset of T2D patients displaying "exercise resistance." Further investigations into the effectiveness of alternate forms of exercise on β-cell function in the T2D patient population are needed. We examined the effect of a novel, 6-wk CrossFit functional high-intensity training (F-HIT) intervention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 40 publications
4
63
2
3
Order By: Relevance
“…Notably, android fat ( P < 0.05), gynoid fat ( P < 0.01), trunk fat ( P < 0.05) and leg fat ( P < 0.0001) were all decreased, while lean tissue remained unchanged. Aerobic fitness (V̇O2 max ) was increased after the F‐HIT training programme (Nieuwoudt et al., ). The 6‐week exercise intervention also resulted in a decrease in DBP ( P < 0.01) and mean arterial pressure (MAP; P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, android fat ( P < 0.05), gynoid fat ( P < 0.01), trunk fat ( P < 0.05) and leg fat ( P < 0.0001) were all decreased, while lean tissue remained unchanged. Aerobic fitness (V̇O2 max ) was increased after the F‐HIT training programme (Nieuwoudt et al., ). The 6‐week exercise intervention also resulted in a decrease in DBP ( P < 0.01) and mean arterial pressure (MAP; P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…We recruited 13 overweight/obese, sedentary adults (5 males, 8 females; age 53 ± 7 years; BMI 34.5 ± 3.6 kg m −2 ; mean ± SD) with clinically diagnosed non‐insulin‐dependent T2D from the local community. This dataset includes 12 participants that were described in a previous publication examining the effect of F‐HIT on pancreatic β‐cell function in individuals with T2D (Nieuwoudt et al., ). All participants were screened with a medical history and physical examination, blood and urine chemistry analyses, and a resting and exercise stress test with 12‐lead electrocardiogram.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proof-of-concept study found that a 6-week CrossFit program reduced body fat, diastolic blood pressure, lipids, and metabolic syndrome Z-score, and increased insulin sensitivity to glucose, basal fat oxidation, VO 2max , and high-molecular-weight adiponectin. 30 HIIT appears to be another effective way to improve metabolic health; and for patients with type 2 diabetes who can tolerate HIIT, it may be a time-efficient, alternative approach to continuous aerobic exercise.…”
Section: Exercise Modalitiesmentioning
confidence: 99%
“…55 And we recently found that a 6-week CrossFit training program improved beta-cell function in adults with type 2 diabetes. 30 …”
Section: Benefits Of Exercise For Specific Metabolic Tissuesmentioning
confidence: 99%